Functional Verification of the Citrate Transporter Gene in a Wine Lactic Acid Bacterium, Lactiplantibacillus plantarum - Yang, Xiangke; Zhao, Lili; Chen, Qiling; Wang, Nan; Shi, Kan; Liu, Shuwen (Frontiers in Bioengineering and Biotechnology, 2022)
Organic acid metabolism by lactic acid bacteria plays a significant role in improving wine quality. During this process, the uptake of extracellular organic acids by transpoters is the first rate-limiting step. However, up to now, there is very little published research on the funtional verification of organic acid transport genes in wine lactic acid bacteria. In this study, a predicted citrate transporter gene JKL54_04345 (citP) by protein homology analysis was knocked out using CRISPR/Cas9-based gene editing system, and then complemented using the modified pMG36e vectors in a major wine lactic acid bacterium, Lactiplantibacillus plantarum XJ25, to verify its function in citrate metabolism for the first time. The results showed that the gene knockout mutant XJ25-ΔcitP lost the ability to utilize citric acid, while the gene complement mutant XJ25-ΔcitP-pMG36ek11-citP fully recovered the ability of citric acid utilization. Meanwhile, citP knockout and complement barely affected the utilization of L-malic acid. These indicate that citP in L. plantarum functioned as citrate transporter and was the only gene responsible for citrate transporter. In addition, two modified plasmid vectors used for gene supplement in L. plantarum showed distinct transcription efficiency. Transcription efficiency of citP in XJ25-ΔcitP-pMG36ek11-citP mutant was 5.60 times higher than that in XJ25-ΔcitP-pMG36ek-citP mutant, and the utilization rate of citric acid in the former was 3.95 times higher than that in the latter, indicating that pMG36ek11 can be used as high-level expression vector in lactic acid bacteria.